2011
DOI: 10.1186/1472-6831-11-32
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of apical periodontitis and endodontic treatment in a Kosovar adult population

Abstract: BackgroundDespite numerous studies on the prevalence of apical periodontitis (AP) and endodontic treatment in diverse geographical populations, there are currently no data on the prevalence of these conditions in populations of adults native to Kosovo. Therefore, little is known about how widespread these conditions are, and whether there is any correlation between root canal treatment and AP. The purpose of our research was to address this anomaly by investigating AP and endodontic treatment in an adult Kosov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
2
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 39 publications
(81 reference statements)
8
46
2
6
Order By: Relevance
“…The results of this study indicated that the prevalence of chronic apical periodontitis increased with age so that the risk of this lesion in patients over 59 years old was approximately 11.604 times greater than that of patients < 20 years old (p < 0.001), which is in line with the findings of Dutta et al [13] and Kamberi et al [15].…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study indicated that the prevalence of chronic apical periodontitis increased with age so that the risk of this lesion in patients over 59 years old was approximately 11.604 times greater than that of patients < 20 years old (p < 0.001), which is in line with the findings of Dutta et al [13] and Kamberi et al [15].…”
Section: Discussionsupporting
confidence: 82%
“…16 The ratio between quality of RF teeth and presence of AP showed results with great amplitude. When the frequency of AP in adequate RF teeth was evaluated in comparison with the total number of RF teeth, the range was from 0.1 26 to 41.6%. 23 In inadequate RF teeth with AP, this frequency ranged from 16.8 24 to 58.5%.…”
Section: Resultsmentioning
confidence: 99%
“…In the evaluation of the periapical status, represented by the presence of AP, the majority of the studies included in this present review 1,9,[16][17][18][19][21][22][23][25][26][27] used the periapical index (PAI) system proposed by Ørstavik et al 28 ( Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the origin of periapical lesions, the risk factors seem to be connected to the quality of coronal sealing and the endodontic treatment performed [11][12]. Furthermore, a high prevalence of endodontic disease recurrence is evident in many parts of the world [13][14][15].…”
Section: Discussionmentioning
confidence: 99%